2022
DOI: 10.1002/wrna.1764
|View full text |Cite
|
Sign up to set email alerts
|

Immune dysregulation and RNA N6‐methyladenosine modification in sepsis

Abstract: Sepsis is defined as life-threatening organ dysfunction caused by the host immune dysregulation to infection. It is a highly heterogeneous syndrome with complex pathophysiological mechanisms. The host immune response to sepsis can be divided into hyper-inflammatory and immune-suppressive phases which could exist simultaneously. In the initial stage, systemic immune response is activated after exposure to pathogens. Both innate and adaptive immune cells undergo epigenomic, transcriptomic, and functional reprogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 154 publications
0
5
0
Order By: Relevance
“…Growing evidence suggests that PTMs can be a cornerstone in regulating cell functions and multiple diseases, including sepsis. However, the mechanisms by which an infection induces specific protein PTMs and protein PTMs lead to inflammatory disorders, cytokine storm, and organ dysfunction remain unclear. We previously reported LPS-induced proteome and acetylome data in vitro and indicated the functional regulation of lysine-acetylated PKM2 in SALD .…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence suggests that PTMs can be a cornerstone in regulating cell functions and multiple diseases, including sepsis. However, the mechanisms by which an infection induces specific protein PTMs and protein PTMs lead to inflammatory disorders, cytokine storm, and organ dysfunction remain unclear. We previously reported LPS-induced proteome and acetylome data in vitro and indicated the functional regulation of lysine-acetylated PKM2 in SALD .…”
Section: Discussionmentioning
confidence: 99%
“…m6A modi cation can orchestrate the development, differentiation, and activation of immune cells, consequently affecting the host defense and in ammatory responses to pathogens 11 . Dysregulated m6A modi cations contribute to the pathogenesis of immune-related diseases 12 . In addition, many studies have reported the role of m6A methylation in programmed cell death including apoptosis, autophagy, pyroptosis, necroptosis, and ferroptosis 13 .…”
Section: Introductionmentioning
confidence: 99%
“…m 6 A modification can orchestrate the development, differentiation, and activation of immune cells, consequently affecting the host defense and inflammatory responses to pathogens [11]. Dysregulated m 6 A modifications contribute to the pathogenesis of immune-related diseases [12]. In addition, many studies have reported the role of m 6 A methylation in programmed cell death including apoptosis, autophagy, pyroptosis, necroptosis, and ferroptosis [13].…”
Section: Introductionmentioning
confidence: 99%